Effect of steam addition on gas turbine combustor design and performance. (5th July 2016) - Xue, Rui; Hu, Chunbo; Sethi, Vishal; Nikolaidis, Theoklis; Pilidis, Pericle
Highlights: Influence of steam addition on combustor design and performance was studied. A combustor design procedure is established and validated by real gas turbines. The dimension of the combustor should be designed larger when steam is added. The variation is highest for components where intense combustion takes place. Total pressure loss and outlet Mach number are deteriorated with steam addition. Abstract: Adding steam influences the combustion process inside the combustor, which should be taken into account during combustor design. The design of combustor has long been the most challenging process. This study integrated the gas turbine performance with the combustor design, and formulated a detailed procedure for single annular combustors with steam addition consideration in particular. To accomplish this, a computer code has been developed based on the design procedures. The design model could provide the combustor geometry and the combustor performance. The inlet parameters for combustor design are obtained and validated through the calculation of gas turbine engine performance provided by our own home code. The model predictions are compared with operational and configuration data from two real engines and show reasonably good accuracy. The influence of steam addition on combustor design is investigated and results showed the variation of geometrical size is highest for components where intense combustion takes place while the design is almost kept the same for components where only pure flow exists. After conforming the feasibility of the combustor design code, we investigated the effects of steam addition on combustor performance. It revealed that steam injection is an effective way to reduce the temperature in the burner while other performance like the total pressure loss would be slightly deteriorated.